Carga e trabalho de enfermagem em unidade de terapia intensiva especializada em queimados - Amadeu, Luciana Mendes [UNESP] (2015)
It is complex to watch people in the Intensive Care Unit Specialized in Burnt, because the lack of the body's largest organ protection, the skin, as well as inhalation injuries may present hemodynamic changes and conditions of vulnerability to infection. The objective of the study is to evaluate the nursing workload, according to the Nursing Activities Score (NAS) in a Intensive Care Unit for the treatment of burned patients; correlate the workload to sociodemographic aspects, clinicals, severity (SAPS 3), burned surface area (BSA%), degree of burn and outcomes and build a Tutorial to instruct and standardize the instrument application. It is an exploratory and descriptive, prospective, quantitative design study, performed in the burn ICU of a large State Hospital, located in e interior city of São Paulo. The unit consists of 4 beds. The population consisted of patients attending the unit from January to June 2014. The sample consisted of 33 patients, with 447 measurements. We obtained the approval of the Ethics Committee under the number CAAE 26679314.2.0000.5411. The workload was assessed by the NAS, prospectively, referring to the last 24 hours. Pearson correlation was used, ANOVA and Tukey tests, all of them with a significance level of 5% (p=0.05). From the total of 33 patients prevailed males with 61%, white 67%, with a stable relationship 54%, 71% with complete primary education, major burn 55%, with accident caused by alcohol and fire 30%, 53% depressed, submitted to intubation and sedated 45% by use of vasoactive medications associated with 45% and 55% with associated inhalation injury. The month of highest incidence of hospitalizations was February with 27%. Regarding the outcome, 61% were discharged to infirmary. The average NAS was 81.94% for the patients who survived and 86.16% for those who died. The hours of nursing in 24 hours was 19.6%. When comparing the nursing hours according to the NAS and COFEN resolution on the ...